2005
DOI: 10.1007/s00198-005-1982-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of pain and fracture incidence after kyphoplasty: 1-year outcomes of a prospective controlled trial of patients with primary osteoporosis

Abstract: Previously, we reported significantly reduced pain and improved mobility persisting for 6 months after kyphoplasty of chronically painful osteoporotic vertebral fractures in the first prospective controlled trial. Since improvement of spinal biomechanics by restoration of vertebral morphology may affect the incidence of fracture, long-term clinical benefit and thereby cost-effectiveness, here we extend our previous work to assess occurrence of new vertebral fractures and clinical parameters 1 year after kyphop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 34 publications
2
66
0
17
Order By: Relevance
“…The data suggest kyphoplasty leads to more rapid return of independent functional mobility at a low risk of complications compared with nonoperative care. In contrast to recent reports questioning the efficacy of vertebral augmentation [4,34], our results support the use of kyphoplasty and confirm the results of other reports [16,24,27,35,40,56,58] that kyphoplasty may accelerate the restoration of patient functional mobility. The improvement in hospital discharge parameters may offset the initially higher cost of treatment and lead to a reduction in the use of medical resources after hospital discharge.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The data suggest kyphoplasty leads to more rapid return of independent functional mobility at a low risk of complications compared with nonoperative care. In contrast to recent reports questioning the efficacy of vertebral augmentation [4,34], our results support the use of kyphoplasty and confirm the results of other reports [16,24,27,35,40,56,58] that kyphoplasty may accelerate the restoration of patient functional mobility. The improvement in hospital discharge parameters may offset the initially higher cost of treatment and lead to a reduction in the use of medical resources after hospital discharge.…”
Section: Discussionsupporting
confidence: 88%
“…The authors concluded kyphoplasty is more effective than medical management of VCF. Despite these recent reports questioning the benefit of vertebral augmentation, the best evidence to date appears to support the use of kyphoplasty for treatment of symptomatic VCF [16,24,27,35,40,56,58]. No large-scale, nationwide studies have been performed to confirm the effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included Articles N=27 of the studies reported effects for the same group of patients and were combined into one analyzable ''study'' (Kasperk/Grafe et al, 4 total [11,12,24,25] and Rousing et al, 2 total [20,26]; see Table 1). This systematic review was reported in accordance with the PRISMA statement [27].…”
Section: Bkp Vs Nsm N=6mentioning
confidence: 99%
“…There is class I evidence to support the superiority of vertebral augmentation procedures (VAPs) over NSM [8][9][10], as well as non-randomized prospective studies [11][12][13], systematic reviews [14][15][16][17][18][19], and numerous retrospective series supporting safety and effectiveness of these procedures. However, recently published randomized controlled trials (RCTs) that showed no superiority of VP over NSM [20] or over a simulated procedure (sham) [21,22] have raised questions regarding the value of VP.…”
Section: Introductionmentioning
confidence: 99%